Growth and yield performance of Pleurotus ostreatus on various lignocellulosic local agro-industrial waste materials mixed with rubber tree sawdust - Fathie, Ahmad Zakil (2024)
Currently, the commercial cultivation of Pleurotus sajor caju using sawdust from rubber tree as the base substrate in Malaysia is popular that cause the increasing of rubber tree sawdust price and demand, affecting the overall production cost. Thus, a new inexpensive alternative substrate yet as effective as rubber tree sawdust is needed to replace the RS as the base substrate for the cultivation of P. sajor caju. Agricultural waste of empty fruit bunch (EFB), palm pressed fibre (PPF), sugarcane bagasse (SGB) or corn cob (CC) and RS were used: as an alternative substrate for the cultivation of P. sajor caju. Four mixture ratios by weight of each agricultural waste; namely 0 + 100%, 25 % + 75%, 50% + 50%, 75% + 25%, and 100% + 0% of agricultural waste: RS were prepared. A 100% RS was used and set as the control substrate. The potential application of spent mushroom substrate (SMS) in production of P. sajor caju mushroom was also investigated. Moreover, the effect of additional charcoal as supporting growing material in the cultivation of the P. sajor caju was also done by using various mixture of agricultural wastes and RS. All mushroom substrates were supplemented with five wt% of wheat bran and 1.5 wt% of calcium carbonate to enhance the mushroom production. All the substrates formulation was placed in polyethylene bag with 15 cm height and sterilized using a sterilization chamber at 100oC for eight hours. After the sterilization was done, all the substrates are left to cool down at room temperature prior to the inoculation of P. sajor caju. Number of days of mycelium growth, number of days of pinhead formation, mushroom formation and harvest time, mushroom yield and physical characteristics such as cap diameter and stipe length were determined. Mineral analysis of the harvested mushrooms from the first harvest were also analyzed for their mineral element content using ICPMS analysis. It is found that the best substrate to obtain a best total weight of fresh mushrooms of 207.96 g/bag and biological efficiency (B.E) of 78.48% was obtained from 50% SGB + 50% RS substrate. Furthermore, the substrate of 50% SMS + 50% RS had a lower average total yield at 156.12g/bag but a higher B.E of 55.76% compared to 100% RS which had an average total yield of 159.67 g/bag and B.E of 53.22%. Although potassium (K) is found to be the most concentrated macro element except 100% RS, all heavy metal concentrations were below the maximum value allowed by WHO/FAO in the first fresh mushrooms harvested from 100% RS, 100% EFB, 100% PPF, 100% SGB, 100% CC and 100% SMS. Furthermore, all the substrates containing charcoal, either 2 wt% or 4 wt%, showed a faster growth of mycelium rather than the substrate without the charcoal addition. Meanwhile, the 100% RS with 2 wt% of charcoal addition substrate produced an average total yield of 203.33 g/bag and B.E of 64.55 % and these values are close to the 50% SGB + 50% RS without charcoal addition substrate with an average of total yield of 207.96 g/bag and the B.E of 78.48%. Therefore, the 50% SGB + 50 % RS without charcoal addition substrate was found to be the best substrate for the cultivation of the P. sajor caju followed by 100% RS with 2 wt% charcoal addition substrate based on the average total yield and B.E. In conclusion, cultivation of mushroom can be done using agricultural waste and the SGB substrate alone or in mixture of SGB and RS is the most suitable for small scale P. sajor caju production.